Anti-inflammatory Activity of Bromelia hieronymi: Comparison with Bromelain - Errasti, María E.; Caffini, Néstor O.; Pelzer, Lilian E.; Rotelli, Alejandra E. (Planta Medica, 2013)
Some plant proteases (e. g., papain, bromelain, ficin) have been used as anti-inflammatory agents for some years, and especially bromelain is still being used as alternative and/or complementary therapy to glucocorticoids, nonsteroidal antirheumatics, and immunomodulators. Bromelain is an extract rich in cysteine endopeptidases obtained from Ananas comosus. In this study the anti-inflammatory action of a partially purified extract of Bromelia hieronymi fruits, whose main components are cysteine endopeptidases, is presented. Different doses of a partially purified extract of B. hieronymi were assayed on carrageenan-induced and serotonine-induced rat paw edema, as well as in cotton pellet granuloma model. Doses with equal proteolytic activity of the partially purified extract and bromelain showed significantly similar anti-inflammatory responses. Treatment of the partially purified extract and bromelain with E-64 provoked loss of anti-inflammatory activity on carrageenan-induced paw edema, a fact which is consistent with the hypothesis that the proteolytic activity would be responsible for the anti-inflammatory action.
Keywords: Bromelia hieronymi; Bromeliaceae; bromelain; anti-inflammatory; plant proteases